2017
DOI: 10.1016/j.ebiom.2017.01.041
|View full text |Cite
|
Sign up to set email alerts
|

The Introduction of Diphtheria-Tetanus-Pertussis and Oral Polio Vaccine Among Young Infants in an Urban African Community: A Natural Experiment

Abstract: BackgroundWe examined the introduction of diphtheria-tetanus-pertussis (DTP) and oral polio vaccine (OPV) in an urban community in Guinea-Bissau in the early 1980s.MethodsThe child population had been followed with 3-monthly nutritional weighing sessions since 1978. From June 1981 DTP and OPV were offered from 3 months of age at these sessions. Due to the 3-monthly intervals between sessions, the children were allocated by birthday in a ‘natural experiment’ to receive vaccinations early or late between 3 and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 17 publications
0
84
0
1
Order By: Relevance
“…Fifth, several studies have shown that mortality is lower when OPV-only rather than the recommended combination of OPV and DTP has been given [49,50].…”
Section: Example: Oral Polio Vaccinementioning
confidence: 99%
See 2 more Smart Citations
“…Fifth, several studies have shown that mortality is lower when OPV-only rather than the recommended combination of OPV and DTP has been given [49,50].…”
Section: Example: Oral Polio Vaccinementioning
confidence: 99%
“…Sixth, two studies of the introduction of DTP and OPV in the rural and urban areas of Guinea-Bissau showed that mortality was higher when DTP-only was administered rather than DTP and OPV simultaneously [50,51]. In other words, OPV appears to have reduced the potential negative effects of DTP.…”
Section: Example: Oral Polio Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…(1)(2)(3)(4) Live vaccines affect the innate immune system beneficially leading to increased response to unrelated pathogens (2) and are associated with lower morbidity and mortality from non-targeted diseases. (1,(3)(4)(5)(6)(7) Studies suggest that live vaccines induce a T-helper 1 cell dominant shift reducing atopic diseases. (4,8,9) In contrast, non-live vaccines can induce tolerance of the innate immune system leading to decreased responses to unrelated pathogens (2) and have been associated with higher morbidity and mortality from non-targeted diseases.…”
Section: Introductionmentioning
confidence: 99%
“…"All currently available evidence suggests that DTP vaccine may kill more children from other causes than it saves from diphtheria, tetanus or pertussis" 1 (Peter Aaby [14])…”
mentioning
confidence: 99%